The Impact of Geopolitical Risk on Corporate Investment: Evidence from Turkish Firms - Tan, Omer Faruk; Cavlak, Hakan; Cebeci, Yasin; Güneş, Necati (The Indonesian Capital Market Review, 2022)
This study analyzes the effects of geopolitical risk on the corporate investment of 164 Turkish manufacturing firms listed in Borsa Istanbul (BIST). The time covers the period from 2005 to 2019, applying the system Generalized Methods of Moments (GMM) estimator. The results indicate that geopolitical risk hurts corporate investment in Turkey. Under uncertainty induced by geographical risk, firms prefer to decline their investment. Additionally, financially constrained (non-dividend, small, young) firms are more negatively affected than financially unconstrained firms. Our findings are robust under alternative measures of geopolitical risk. Overall, this study reveals that geopolitical risk is a significant uncertainty affecting the investment decisions of manufacturing firms in Turkey